STRATEGI KOMUNIKASI PEMERINTAH DAERAH LOMBOK UTARA DALAM MEMBANGUN HUBUNGAN MASYARAKAT YANG KUAT (ANALISIS TEORI BUDAYA KUAT TERENCE DEAL DAN ALLAN) - RITA ARISANDY; SANDI JUSTITIA PUTRA; IRMA EL-MIRA HUSBUYANTI; DENDA DEVI SARAH MANDINI MANDINI; ANISA PURWA NINGRUM; NI WAYAN MARIASEH (GANEC SWARA, 2024)
Governments that have good relations with society tend to gain higher trust from their citizens. This trust is important for government legitimacy, which in turn increases compliance and support for government policies and programs. It is hoped that this research can help the North Lombok Regency Regional Government in developing an effective communication strategy that can be implemented in building strong community relations. Using the strong cultural theoretical framework of Terence Deal and Allan Kennedy. This research uses a qualitative approach with a literature study method. The data used comes from previous research, literature studies, and is relevant. By implementing strong cultural elements in its communications strategy, the North Lombok Regency Regional Government can build stronger relationships with the community, thereby increasing trust, participation and support for government programs. By instilling core values, elevating local heroes, holding rituals and ceremonies, utilizing informal networks, and building a strong narrative, the North Lombok Regency Regional Government can increase community trust and support. By integrating these elements, the North Lombok Regency Regional Government can create an environment that supports effective communication and builds stronger trust with the community. This will contribute to increased public participation and support for government programs, thereby bringing greater benefits to local communities